THROMBOMODULIN OVEREXPRESSION SURROUNDING A SUBEPIDERMAL BULLOUS ALLERGIC DRUG ERUPTION - Ana Maria Abreu Velez; Garin Barth; Michael S. Howard (Our Dermatology Online, 2013)
Blistering drug eruptions and drug-induced anaphylaxis and hypersensitivity syndromes are among the most serious types of adverse drug reactions. We report a 69 old female patient who was using multiple medications and presented with a two month history of recurrent blisters, pustules and crusts. The patient was evaluated by a dermatologist, and biopsies for hematoxylin and eosin (H&E) examination, as well as for direct immunofluorescence (DIF) and immunohistochemistry (IHC) were performed. The H&E examination revealed a subepidermal blister with numerous luminal eosinophils, as well as a dermal superficial and deep, perivascular infiltrate of lymphocytes, histiocytes and eosinophils. The DIF revealed a linear positive staining on the subepidermal interior of the blister with IgG, IgA, IgM, IgD, Complement/C4, lambda light chains, fibrinogen, and albumin; staining was noted in the basement membrane zone, and also focally present around dermal blood vessels and eccrine glands. The dermal staining colocalized with anti-p0071 (Plakophilin 4). We also observed overexpression of thrombomodulin in adjacent epidermal keratinocytes, as well as in the upper dermal blood vessels; its presence may be linked to mitigation of inflammation. With the increased medications that many patients are taking orally and are using topically, overall drug reaction patterns seem to be more complex than previously described.